Trajectory Analysis of Orthostatic Hypotension in Parkinson’s Disease: Results From Parkinson’s Progression Markers Initiative Cohort - Chen, Kui; Du, Kangshuai; Zhao, Yichen; Gu, Yongzhe; Zhao, Yanxin (Frontiers in Aging Neuroscience, 2021)
Background: Orthostatic hypotension (OH) in Parkinson’s disease (PD) can lead to falls, impair quality of life and increase mortality. Trajectory analysis of OH could be useful to predict and prevent hypotension incidence early. Methods: Longitudinal data of 660 PD patients with disease duration up to 12 years were extracted from an integrated PD database. We used latent class mixed modelling (LCMM) to identify patient subgroups, demonstrating trajectories of orthostatic blood pressure (BP) changes over time. The optimal number of subgroups was selected by several criteria including the Bayesian Information Criterion. Baseline information comparison between groups and backward stepwise logistic regression were conducted to define these subgroups’ distinguishing characteristics and to investigate the predictors for BP trajectory. Results: We identified three trajectories for each orthostatic change of systolic blood pressure (ΔSBP): Class 1 (the increasing class) consisted of 18 participants with low ΔSBP that increased continuously during follow-up; Class 2 (the low-stable class) consisted of 610 participants with low ΔSBP that remained low throughout follow-up; Class 3 (the high-stable class) consisted of 32 participants with high ΔSBP at baseline that was relatively stable. Several parameters differed among subgroups, but only male sex (OR=4.687, 95% CI=1.024-21.459), lower supine diastolic blood pressure (DBP) (OR=0.934, 95% CI=0.876-0.996) and lower level of total protein at baseline (OR=0.812, 95% CI=0.700-0.941) were significant predictors of an increasing ΔSBP trajectory. Conclusion: This study provides new information on the longitudinal development of ΔSBP in PD patients with distinct trajectories of rapidly increasing, low-stable and high-stable. Male sex, lower supine DBP and lower total proteins help to identify the rapidly increasing class.